Implementasi Sistem Pendukung Keputusan Pemberian Reward Karyawan Menggunakan Metode Weighted Product: Studi Kasus: PT XYZ Palembang - Adelia Anjelina; Yulistia Yulistia (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
PT XYZ is a private company in Palembang that supplies medical devices and equipment. This company conducts performance assessments every year to provide appropriate rewards in the form of gifts, bonuses or incentives to employees. In carrying out the performance assessment process for providing employee rewards, it is still done manually. This process is inefficient because it takes a lot of time, is prone to errors in calculation and it is not clear which aspects of the criteria are important. By using the Weighted Product methodology, this study tries to create a decision support system (DSS) that will simplify this evaluation procedure. This application is made website-based, using the laravel framework with the Iterative system development method. The results obtained indicate that the system can help companies improve efficiency by conducting automatic assessments, providing measurable weights, transparently and using the Weighted Product method for more accurate assessments. Overall, the system developed meets the research objectives.